RISK ANALYSIS OF TSUNAMI AND COASTAL EROSION IN MENTAWAI ISLAND - ZULFATI SHABRINA (NIM: 25117016), FATHIA
The Mentawai islands located near the Sumatra subduction zone which is currently accumulating strains, causing high potential for earthquakes and tsunamis. Besides the tsunami waves, the Mentawai Island is also prone to high waves due to the wind in the Australia monsoon period. This coastal hazard potential cause significant risk like physical damage or loss of life. Accordingly, disaster risk reduction program in coastal areas is indispensable in advance for the next destructive coastal hazard event. This need is answered by conducting disaster risk analysis as the first step in disaster identification in the Mentawai Islands and as a reference in conducting further risk management. However, a comprehensive coastal disaster risk analysis is not yet available in the Mentawai. Thus, coastal disaster risk analysis especially tsunami and abrasion in the Mentawai Islands is important to be done as the purpose of this research. If disaster risk analysis is not carried out, the disaster consequences will be higher and will have an impact on economic losses in a country. The approach used in conducting coastal disaster risk analysis is to incorporate hazard components which are tsunamis and abrasions as well as components of vulnerability which are social aspect and physical aspect. Social aspect is population density and physical aspect is building. Population density is obtained by modeling with a static approach and a dynamic approach with day and night scenarios. In the tsunami risk analysis, the risk is obtained using quantitative approaches presented with the summing and characterization of risky elements consist of the number of buildings and the number of people affected to estimate the fatality and damaged buildings. In abrasion risk analysis, the risk is obtained using a qualitative approach by combining the multi-dimensional aspects of vulnerability as well as the hazards derived from the identification of the abrasion driving physical variable. The calculation results are presented in the form of qualitative class which allows comparing the level of risk of abrasion among administrative units. From this research, estimation of tsunami fatality in the Mentawai Islands is 7,212 people for static approach, 11,839 for daytime approach, and 13,603 for night-time approach from a total population of 85.295 people. Estimated buildings damaged by the tsunami in Mentawai Islands as many as 4,253 buildings from 15,935 buildings affected. The eastern Mentawai coast has a wider area of risk of abrasion than the west coast due to the influence of the Australian monsoon. The result of this risk analysis is allowing disaster managers to determine the most effective and appropriate treatment options, especially those related to tsunami and abrasion disaster management such as determining the location of the evacuation site and the location of the construction of an abrasion barrier.